FORMALDEGID–KETON KONDENSATSIYASI ASOSIDA KOMPOZIT MATERIALLAR OLISH - To‘htaboyeva Muhayyo Maxfurali qizi; M. A. Ahmadaliyev (TADQIQOTLAR, 2026)
Abstract: Formaldehyde–ketone condensation reactions play an important role in the synthesis of polymeric and composite materials with improved mechanical, thermal, and chemical properties. This study investigates the formation of composite materials based on formaldehyde–ketone condensation products, focusing on reaction mechanisms, synthesis conditions, and material characteristics. The obtained composites demonstrate enhanced strength, thermal stability, and resistance to chemical agents, making them suitable for application in construction, coatings, and industrial materials. The results confirm that controlling reaction parameters significantly affects the structure and performance of the resulting composites.